Meningkatkan Peran Jaksa dalam Pembaharuan Hukum Pidana dan Menangani Kasus Penyalahgunaan Narkotika Golongan 1 - Bintang, Cantika Ramadhani; Widjajanti, Ermania (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
In handling class I narcotics abuse cases, a very precise role of the prosecutor is needed because in cases of narcotics abuse, the perpetrators are often immediately sent to prison, this is very ineffective. In this case, the role of the prosecutor is very important in handling cases to take legal action. In this case, there is a need for a policy of criminal law reform. The type of research used by the author is normative juridical which is descriptive in nature with secondary legal material sources using qualitative data collection techniques. As a result of this research, the author formulates how to increase the role of prosecutors in implementing criminal law reforms to handle class I narcotics abuse cases, then what are the main challenges faced by prosecutors in implementing criminal law reforms in law enforcement in class I narcotics abuse cases.